Evaluation of patient communication skills of dental students at Islamic Azad university of Isfahan in 2021 - Soheila Khalili; Hajar Shekarchizadeh; Afsaneh Pakdaman (Tehran University of Medical Sciences, 2022)
Background and Aims: For dental students, communication skills are essential to effectively transfer the necessary information to the patient and meet the patient's needs and expectations. Therefore, this study was conducted to determine the patient communication skills of dental students at Islamic Azad university of Isfahan in 2021. Materials and Methods: In the present cross-sectional analytical study, an online standardized questionnaire DCCC (Dental consultation communication checklist) was provided to all clinical dental students applying a census sampling method. In total, from 248 clinical dental students, 230 students participated in the study (response rate=92.7%). The questionnaire included five dimensions of introduction, medical history, clinical examination, closure and patient. In order to determine the patient communication skills, its dimensions, and the association between patient communication skills and students' demographic characteristics, friedman test, analysis of variance, independent t-test and a linear regression model were used for statistical analysis. Results: The mean score of total communication skills of the students (117.16±15.6) was above average which was obtained from the maximum score of 155. There was a significant difference between the dimensions of communication skills (P<0.001). The highest scores were assigned to the clinical examination, patient, medical history, introduction and closure, respectively. No significant relationship existed between the score of students' communication skills with gender (P=0.08), age (P=0.17), marital status (P=0.19), and educational background in psychology (P=0.07). No significant relationship revealed between the total score of communication skills (P=0.92) and its dimensions (introduction P=0.79, medical history P=0.90, clinical examination P=0.77, closure P=0.35, and patient P=0.85) with the students' academic year. Conclusion: The total score of dental students' communication skills and all its dimensions was above average. However, students reported poorer performance in dimensions of introduction and closure than the other dimensions. Therefore, it is recommended to design and implement educational interventions specially to improve the dimensions of introduction and closure.